Marie and Otto Neurath: “Good Fellows in Science and Love” - Lyon, E. Stina (Serendipities. Journal for the Sociology and History of the Social Sciences, 2022)
This article presents the story of a partnership with a major impact on the development of visual means of communicating social science findings as a means to facilitate universal participatory democracy. It aims to highlight the neglected role of Marie Neurath as data “transformer” in the origins of the visual language of ISOTYPE. It locates the partnership in the context of the politically and culturally turbulent times of anti-Semitism and forced migration during the middle decades of the 20c, and highlights Marie’s contributions after the death of her partner. It concludes with a call for a more multifaceted and culturally inclusive picture of disciplinary history in the social sciences.